PERANCANGAN SAKLAR OTOMATIS MENGGUNAKAN MICROCONTROLLER BERBASIS TEKNOLOGI INTERNET OF THINGS (IOT) - Sofia Pinardi; Emilia Roza; Muhammad Alviani; Akbar Shah Rukh Khan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
Water and electricity are very vital human needs; it’s necessary to use them efficiently. The use of a water reservoir is a solution, and the machine can be set ON OFF using a float indicator. When the machine is ON, it fills the water, and is full, switch OFF and ON again when the water reaches a certain height. The ON-OFF process of the pump machine automatically occurs when the power plugged in; this condition is very dangerous, causing heat, and empty house, switch is always ON. Remote automatic is required. This automatic uses a quasi-experimental method with three stages, namely making a design, conducting tests, and analysing test results. Internet of Things (IoT) technology, based on a microcontroller, can implement an automatic switch for controlling and operating electronic devices remotely online and in real time via mobile (cellphone). The use of a microcontroller will be configured to connect to the Ubidots application.